Genesis of Juvenile Pedagogy Development - Chaltseva, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Modern approaches to studying the phenomenon "youth" in the view of overcoming scientific isolation and lack of unity make it necessity to develop complex juvenile knowledge. Scientific and pedagogical knowledge concerning youth is a component of juvenile knowledge. The article is devoted to the issue of forming and developing an integrative branch of pedagogical knowledge of youth - juvenile pedagogy. The author presents the results of historical-pedagogical analysis of Juvenile pedagogy development as part of pedagogical theory and practice history. Criteria for stage development of juvenile pedagogy are allocated. The author gives detailed account of each period. The article also includes analysis of papers by Russian teachers on problems of educating younger generation, development of pedagogical knowledge of youth. Main directions of juvenile pedagogy development are stated.